A pretreatment nomogram for prediction of biochemical failure after primary cryoablation of the prostate. Issue 13 (14th July 2015) - Elshafei, Ahmed; Kovac, Evan; Dhar, Nivedita; Levy, David; Polascik, Thomas; Mouraviev, Vladimir; Yu, Changhong; Jones, J. Stephen
<x xml:space="preserve">Abstract</x> Background To create a predictive nomogram for biochemical failure following primary whole‐gland cryoablation of the prostate for localized prostate cancer (LPCa). Methods We retrospectively analyzed 2, 242 patients from the Cryo On‐Line Database (COLD) who were treatment naive and had undergone primary whole gland cryoablation of the prostate for biopsy‐confirmed LPCa. Kaplan–Meier (KM) curves estimating 5 year biochemical progression‐free survival (bPFS) were generated. Multivariable Cox proportional hazards analysis (CoxPH) was performed in order to construct the nomogram. The nomogram was internally validated using the bootstrap technique. Results Overall, the KM estimated 5 year bPFS was 72.8%. Stratified by D'Amico risk, The KM estimated 5 year bPFS was 82.6%, 71.1%, and 57.8% for low‐, intermediate‐, and high‐risk groups, respectively. Statistically significant predictors of biochemical outcomes from CoxPH analysis were pre‐treatment prostate specific antigen (PTPSA) (P < 0.001), total prostate volume (P = 0.004), clinical stage (P = 0.034), and Gleason score (0.004). A nomogram for predicted 5 year biochemical progression free probability was constructed with a concordance index of 0.652. An online risk calculator was also generated. Conclusions To the best of our knowledge, this is the first predictive nomogram for biochemical outcomes after primary whole gland cryoablation of the prostate using socio‐demographic, pretreatment, clinical, and prostate biopsy data. Our nomogram and online risk calculator can guide both patients and urologists for shared decision making regarding definitive treatment options. Prostate 75:1447–1453, 2015. © 2015 Wiley Periodicals, Inc.